Heterosis for seed yield and its components in jatropha (Jatropha curcas L.) - A K M, Aminul Islam; Anuar, Nurina; Yaakob, Zahira; Osman, Mohamad (Global Science Books, 2011)
Heterosis was determined in a population obtained from a 6 × 6 half diallel cross of jatropha genotypes for seed yield per plant and its components traits at the experimental station of Universiti Kebangsaan Malaysia during February 2010 to April, 2011. Results showed that variations for days to flowering, days to fruit maturity, number of primary branches per plant, seed yield per plant and its component characters was significant. Both positive and negative heterosis was found for seed yield per plant. High mid-parent heterosis (254.13%) and better parent heterosis (202.36%) were found for seed yield per plant in the cross P2 × P5 and P1 × P3, respectively. Small heterosis over mid-parent was also found for days to flowering and days to fruit maturity. The parents P1, P2, P3 and P5 were found to be superior for seed yield and its components when used in crosses. Considering earliness and seed yield per plant the hybrid combinations P1 × P2, P1 × P3, P2 × P5 and P4 × P6 were promising. These combinations could be selected for the development of hybrid varieties in Jatropha curcas.